Depiction of woman in Vijay Tendulkar's Novel "Silence! The court is in session" (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Vijay Tendulkar has constantly raised his voice against shameful acts distributed to poor people and the survivors of organized violence in a splendid way. Women make a fundamental piece of the hindered bunch in his dramatizations. He uncovered the fraud of the male chauvinists and seriously assaults the trick moral principles of the male centric working class society of contemporary India. In the Silence The Court is in Session, a phase commendable play set in a climate of interest, false reverence, avarice and fierceness, the exploited individual turns out to be a woman who set out to oppose the socio-moral code of sexuality outlined by men to control the collection of women. It is intriguing to see the value in the play from the Indian women's activist point of view. The play centers around Indian working class life in metropolitan culture, male authority, mind of enduring women, and self centered, hypocritical nature of men. The shortfall of any evident arrangement toward the finish of the play underlines the weightiness of the mind boggling circumstance where a contemporary instructed Indian woman is denied her singularity and freedom